Criteria for the Development of Economic Competence in Students - Saidkulova Firuza Farmonovna (Zien Journals, 2023)
The article sets out the position of authors regarding the process of forming the economic competencies of students from the point of view of the activity approach, the possibility of the influence of labor education through specified social functions on the economic culture of the younger generation
Keywords: Education; professional competences; economic competence; economic culture